Iron, zinc and iodide status in Mexican children under 12 years and women 12-49 years of age: a probabilistic national survey Estado de hierro, zinc y yodo en niños menores de 12 años y en mujeres de 12-49 años de edad en México: una encuesta probabilística nacional - Salvador Villalpando; Armando García-Guerra; Claudia Ivonne Ramírez-Silva; Fabiola Mejía-Rodríguez; Guadalupe Matute; Teresa Shamah-Levy; Juan A Rivera (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To describe the epidemiology of iron, zinc and iodide deficiencies in a probabilistic sample of Mexican women and children and explore its association with some dietary and socio-demographic variables. MATERIAL AND METHODS: We carried out in 1999 an epidemiological description of iron (percent transferrin saturation, PTS, <16%), serum zinc (<65ug/dl) and iodide (<50 ug/l urine) deficiencies in a probabilistic sample of 1,363 Mexican children under 12 years and of 731 women of child-bearing age. Serum iron, Total Iron Binding Capacity (TIBC) and zinc were measured by atomic absorption spectrometry, and urinary iodide by a colorimetric method. Logistic regression models explored determinants for such micromineral deficiencies. RESULTS: Iron deficiency was higher (67%) in infants <2 years of age. Prevalence declined (34-39%) at school age. The prevalence for iron deficiency in women was 40%. Zinc deficiency was higher in infants <2 years of age (34%) than in school-age children (19-24%). Prevalence in women was 30%, with no rural/urban difference. In women the likelihood of iron deficiency decreased as SEL improved (p=0.04) and increased with the intake of cereals (p=0.01). The likelihood of low serum zinc levels was greater in women and children of low socioeconomic level (SEL) (p<0.02 and p=0.001) iodide deficiency was negligible in both children and women. CONCLUSIONS: The data shows high prevalence of iron deficiency- specially in infants 12 to 24 months of age. It is suggested that in older children and women 12 to 49 years of age that iron bioavailability is low. The prevalence of zinc deficiency was also very high. OBJETIVO: Describir la epidemiología de las deficiencias de hierro, zinc y yodo en una muestra probabilística de mujeres y niños mexicanos y analizar algunas asociaciones con factores dietéticos y sociodemográficos. MATERIAL Y MÉTODOS: Descripción epidemiológica de las deficiencias de hierro (Porcentaje de saturación de transferrina <16%), zinc (<65ug/dl) y yodo (<50ug/l orina) en una muestra probabilística de 1363 niños y 731 mujeres. Las concentraciones séricas de hierro, y la capacidad total de saturación de hierro y zinc se midieron por espectrometría de absorción atómica, y el yodo por un método colorimétrico. Los determinantes de tales deficiencias se estudiaron mediante modelos de regresión logística. RESULTADOS: La deficiencia de hierro fue mayor (67%) en niños <2 años de edad. La prevalencia disminuyó en los escolares (34-39%). La prevalencia de deficiencia de hierro en mujeres fue de 40%. La deficiencia de zinc fue mayor en niños <2 años de edad (34%) que en escolares (19-24%). La prevalencia en mujeres fue de 30%, sin diferencia rural/urbana. La probabilidad de tener deficiencia de hierro en mujeres disminuyó con el nivel socio-económico (p=0.04) y aumentó con la ingestión de cereales (p=0.01). La probabilidad de tener concentraciones bajas de zinc sérico fueron mayores en mujeres de nivel socioeconómico (SES) bajo (p=0.02 y p=0.001). La prevalencia de deficiencia de yodo fue casi inexistente tanto en niños como en mujeres. CONCLUSIONES: Los datos demuestran una alta prevalencia de deficiencia de hierro, especialmente en niños de 12 a 24 meses de edad. Se sugiere que en niños mayores y en mujeres de 12 49 años existe una baja biodisponibilidad de hierro. La deficiencia de zinc fue tambien muy alta.